The contribution of fire damage to restricting high mountain Polylepis australis forests to ravines: Insights from an un-replicated comparison - Alinari, Julieta; Von Müller, Axel; Renison, Daniel (2018)
High mountain forests are often restricted to ravines and much debate has existed on the explanations of this distribution, with arguments ranging from abiotic site conditions being more favorable in ravines to there being reduced herbivory or reduced fire frequency and damage in ravines. We aim at understanding the contribution of fire damage and provide data to help test the hypothesis that fires are less damaging and that trees recover faster in ravines as compared to ridge sites. We evaluated crown damage, post-fire survival, regeneration by resprouts and seeds, and browsed stems in burned and unburned control Polylepis australis trees situated in a ravine and in a ridge forest in the west slope of the mountains of Central Argentina. The proportion of the tree crown scorched by fire was 28 % higher on the ridge than in the ravine (94.3 ± 1.9 % and 66.1 ± 4.5 %, respectively) and was negatively related to tree height which was lower on the ridge. Survival was not differentially affected, but post-fire re-growth and establishment through seeds was lower in the ridge as compared to the ravine. Browsed stems were about twice as frequent in the ridge as in the ravine, more so in the resprouting burned trees. Our study provides evidence that forests are restricted to ravines in part because the effects of fires are less severe at these sites than in ridges, which adds to other possible causes like reduced livestock use of ravines, enhanced regeneration by seed and faster tree growth within ravines all of which are probably mediated by abiotic factors